2020
DOI: 10.1016/j.geotexmem.2019.103499
|View full text |Cite
|
Sign up to set email alerts
|

Response of pavement foundations incorporating both geocells and expanded polystyrene (EPS) geofoam

Abstract: The suitability of geocell reinforcement in reducing rut depth, surface settlements and/or pavement cracks during service life of the pavements supported on expanded polystyrene (EPS) geofoam blocks is studied using a series of large-scale cyclic plate load tests plus a number of simplified numerical simulations. It was found that the improvement due to provision of geocell constantly increases as the load cycles increase. The rut depths at the pavement surface significantly decrease due to the increased later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(4 citation statements)
references
References 113 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…The achieved density of the material was around 18.61 kN/m 3 (118.5 pcf), which is much lower than the MDD value owing to the dry condition. Previous studies have demonstrated that expanded polystyrene (EPS) geofoams can be used as a uniform subgrade material with relatively low strength [42,43]. Thus, a 15.2 cm (6-in.)…”
Section: Large-scale Testbed Equipped With Be Field Sensorsmentioning
confidence: 99%
“…The achieved density of the material was around 18.61 kN/m 3 (118.5 pcf), which is much lower than the MDD value owing to the dry condition. Previous studies have demonstrated that expanded polystyrene (EPS) geofoams can be used as a uniform subgrade material with relatively low strength [42,43]. Thus, a 15.2 cm (6-in.)…”
Section: Large-scale Testbed Equipped With Be Field Sensorsmentioning
confidence: 99%
“…Han et al 25 and Latha and Somwanshi 24 adopted the diamond pattern to simulate the geocell shape. Further, Leshchinsky and Ling 26 , Biabani et al 27 , Ngo et al 28 , Siabil et al 29 used the square and hexagon pattern to calculate. The honeycomb shape (actual shape) was also adopted in recent years 17 , 19 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…et al [25] and Siabil, S.M.A.G. et al [26] also conducted research on the interaction between soil and geocells with fruitful results. Based on existing mechanical models of and experience with geocells, the above research has explored the interaction and relationship between the geocell structure and soil layer.…”
Section: Introductionmentioning
confidence: 99%